(untitled) (Historia, 2021)
History textbooks have a significant role to play, especially in South African classrooms, where many teachers have no access to any other media or subject knowledge. The importance of textbooks was also highlighted by the Report of the History / Archaeology Panel to the Minister of Education, which emphasised that "history textbooks cannot but remain central to the cause of an improved history education". This was more recently echoed in a speech by the Minister of Basic Education, Angelina Motshekga, who opined that the textbook is the most effective tool to ensure better quality instruction. Against this background, this article aims to show how texts discursively construct or encode a cultural mindset prevailing in a particular Zeitgeist, namely as represented in some of the recently published history textbooks for grade 11. In the table below the textbooks used in this study are identified.